2010
DOI: 10.1186/1758-2652-13-23
|View full text |Cite
|
Sign up to set email alerts
|

AIDS‐associated Kaposi's sarcoma is linked to advanced disease and high mortality in a primary care HIV programme in South Africa

Abstract: BackgroundAIDS-associated Kaposi's sarcoma is an important, life-threatening opportunistic infection among people living with HIV/AIDS in resource-limited settings. In western countries, the introduction of combination antiretroviral therapy (cART) and new chemotherapeutic agents has resulted in decreased incidence and improved prognosis of AIDS-associated Kaposi's sarcoma. In African cohorts, however, mortality remains high. In this study, we describe disease characteristics and risk factors for mortality in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
78
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 15 publications
19
78
1
4
Order By: Relevance
“…We found good survival rates of KS patients in routine care, treated with ART and chemotherapy (ABV or oral VP16) and/or radiotherapy for selected patients. The overall one-year survival rate of 78.5% is comparable to survival estimates from other South African studies [8,9,16] , including a clinical trial that used similar chemotherapy regimens [9] . An observational study in the U.S. estimated two-year survival rates comparable to what we found in the late ART period in South Africa (81% and 79%, respectively) [17] .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We found good survival rates of KS patients in routine care, treated with ART and chemotherapy (ABV or oral VP16) and/or radiotherapy for selected patients. The overall one-year survival rate of 78.5% is comparable to survival estimates from other South African studies [8,9,16] , including a clinical trial that used similar chemotherapy regimens [9] . An observational study in the U.S. estimated two-year survival rates comparable to what we found in the late ART period in South Africa (81% and 79%, respectively) [17] .…”
Section: Discussionsupporting
confidence: 69%
“…The advent of ART dramatically decreased KS incidence, morbidity and mortality in high income countries [24] . South Africa addressed its large HIV epidemic by implementing a national ART programme [5–7] , but studies in the early ART era showed that KS morbidity and mortality were still high in South Africa, largely because ART coverage was still too low, and patients with KS were diagnosed late and many who needed chemotherapy did not receive it [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Overall cumulative survival was 69% at 1 year and 64% at 2 years, similar data being reported from a primary care HIV programme in South Africa [15]; however, the survival in our study proved to be lower compared to data reported from Chelsea and Westminster Hospital in London, UK [16]. Using Stebbing's prognostic index for AIDS-associated KS [8] regarding the probability of survival, we found similar values compared to Stebbing's study.…”
Section: Discussionsupporting
confidence: 53%
“…(8) Kaposi sarcoma(KS) and Non Hodgkin's lymphoma(NHL) on the other hand are not vaccine preventable therefore early diagnosis is very essential. (9) Factors that have been found to be important in the control and reduction in the incidence of KS and NHL among HIV infected patients are high CD4 level, initiation on HAART and early detection. (10,11) Although these cancers are AIDs defining, most infected patients are not aware of the symptoms to expect therefore they do not look out for them despite being at risk.…”
Section: Introductionmentioning
confidence: 99%